Juridical Review on Confirmation of Unregistered Marriage (A Case Study of Palu Religious Court) - M. Bahtiar Tahir; Sahabuddin Sahabuddin; Marzuki Marzuki (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2019)
The research problem formulated was concerning judges’ consideration in determining the confirmation of unregistered marriage at Palu Religious Court as well as a juridical review on the judges’ consideration. The purpose of this research was revealing judges’ consideration in determining the confirmation of unregistered marriage at Palu Religious Court as well as a juridical review on the judges’ consideration. This research used field research methods with a quantitative approach at Palu Religious Court. The data source was coming from observation, interview, and written sources. The writer used observation, interview, and documentation methods in collecting the data. The research findings were that judges’ consideration in Palu Religious Court in determining the confirmation of unregistered marriage generally was already following the rules existing. However, Palu Religious Court did not consider the age of the couples of unregistered marriage in which when they held a marriage contract, evasion of law related to the marriage age of the couples was feared to happen for those holding the confirmation of unregistered marriage. The research implication was that the government should revise the marriage laws an include criminal elements for the couple unregistered marriage. The government also should apply a marriage amnesty program for the couple holding unregistered marriage with a certain period and then apply criminal law for the peoples who are marriage unregistered.